The Role of Islamic Economic Principles in the Formation of Public Policy - Anisa Lestari; Nurul Layali; Fahriya; Mashudi (Penerbit Hellow Pustaka, 2025)
By incorporating sharia values into the social and economic system, the concept of Islamic economics is essential in the development of public policy. In order to put Islamic economic ideas into practice, the creation of an economic system based on Islamic principles must take precedence. The aim of this research is to examine how important legal sources are in influencing and guiding the development of Islamic financial institutions. The overarching approach to examining this issue takes into account the basic ideas and origins of Islamic law, the principles of Islamic economics, and how they are used in the process of creating appropriate economic institutions. The study also covers the basic principles of Islamic economics, including distributive justice, the prohibition of usury, and the importance of zakat and waqf, which serve as the foundation for the formation of economic organizations. Thus, this research contributes to further understanding of the importance of legal sources in the formation of Islamic economic institutions and the effective integration of Islamic principles into the modern economic system.